Pengembangan Video Pembelajaran Berbasis Literasi Digital Mitigasi Bencana Banjir dan Tanah Longsor - Padhila Bahar, Nurul; Ashar, H. Hasbullahair; Suhardiman, Suhardiman (Al-Khazini, 2024)
This research aims to determine the development of digital literacy-based learning videos mitigating flood and landslide disasters that meet valid and effective criteria. This type of research is research and development (R&D) with the DDD-E development model consisting of the stages of decide, design, develop, and evaluate. The subject of this study consisted of 2 validators, 1 educator and 22 students of class VII Junior High School Negeri 1 Masamba. The determination of the validity criteria of the magazine uses the aiken V index test with three components of material expert assessment criteria, namely material, presentation, and language aspects, as well as three media expert assessment criteria namely display, sound and text, and presentation. The results of this study showed that the video met the validity criterion with aiken index values V= 0.83 and V=0.81. The effectiveness rate of the magazine showed that 79% of the overall number of learners and 100% of educators responded very positively after using the magazine. In addition, learning results obtained by learners after using digital literacy-based learning videos based on flood and landslide disaster mitigation were obtained 100% of learners obtained learning knowledge above KKM and in test analysis t-1 samples obtained a significant value of 2 tailed < 0,05. Based on these data it can be concluded that digital literacy-based learning videos of flood and landslide disaster mitigation are valid and effective.